A Twist in the Tale - Archer, Jeffrey (London HarperCollins Publishers, 1988)
Twelve short stories with a twist in the ending from Jeffrey Archer, the author of "Not a Penny More, Not a Penny Less", "Kane and Abel" and, most recently, the play, "Beyond Reasonable Doubt".
Keywords: Short stories -- Short stories, English. -- Irony